PROFIL PENGAWAS SEKOLAH DASAR DI UNIT PELAKSANA TEKNIS DINAS PENDIDIKAN - Yetmawati Yetmawati (Manajer Pendididikan, 2015)
The purpose of this research is to describe the profile of school attentionship in Unit Technic Implementation Education Elementary of District Curup Rejang Lebong Region. This study is description research. The result of the research show that: (1) education of school attentionship in elementary school, there is schhool attentionship doesn’t continue high education; (2) experience of school attentionship in elementary school is good; (3) the school attentionship in elementary school according to education ministry standard; (4). There effort of school attentionship to enhance competency.Keywords: profile, school attentionship